2007
DOI: 10.1242/jcs.03308
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome c oxidase maintains mitochondrial respiration during partial inhibition by nitric oxide

Abstract: Nitric oxide (NO), generated endogenously in NO-synthase-transfected cells, increases the reduction of mitochondrial cytochrome c oxidase (CcO) at O2 concentrations ([O2]) above those at which it inhibits cell respiration. Thus, in cells respiring to anoxia, the addition of 2.5 μM L-arginine at 70 μM O2 resulted in reduction of CcO and inhibition of respiration at [O2] of 64.0±0.8 and 24.8±0.8 μM, respectively. This separation of the two effects of NO is related to electron turnover of the enzyme, because the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 25 publications
0
47
0
Order By: Relevance
“…In the first situation, the [O 2 ] is not critical. We have previously demonstrated that increases in [NO] relative to [O 2 ] that are not yet sufficient to inhibit respiration reduce cytochrome c oxidase and that the recruitment of excess capacity of this enzyme is able to maintain O 2 consumption in the cell (31). Only when the NO:O 2 ratio increases to a point at which this excess capacity is fully used does inhibition of respiration ensue.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the first situation, the [O 2 ] is not critical. We have previously demonstrated that increases in [NO] relative to [O 2 ] that are not yet sufficient to inhibit respiration reduce cytochrome c oxidase and that the recruitment of excess capacity of this enzyme is able to maintain O 2 consumption in the cell (31). Only when the NO:O 2 ratio increases to a point at which this excess capacity is fully used does inhibition of respiration ensue.…”
Section: Discussionmentioning
confidence: 99%
“…Induced cells were harvested and counted as described in ref. 31, then placed in a water bath at 37°C before measurement in the visible light spectroscopy (VLS) chamber.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations